Peran Kepemimpinan di Puskesmas terhadap Kinerja Organisasi dan Kualitas Pelayanan Kesehatan - Andy Amir; Oka Lesmana; Dwi Noerjoedianto; Andi Subandi (Journal of Telenursing (JOTING), 2021)
This study aims to see the role of leadership in improving performance and the role of services at the Puskesmas. The method used is qualitative and quantitative with a community-based participatory approach involving 20 Heads of Health Centers in Jambi City and 197 Puskesmas staff. The results showed that 58% of respondents strongly agreed that leadership at the Puskesmas has a vital role in improving performance and service quality and 42% consider it quite important. The role of the Puskesmas leadership is not optimal in enhancing organizational performance, including staff training, staff involvement in decision-making, and giving rewards and punishments. Meanwhile, the leadership role is good enough to improve Puskesmas services, including reliability, responsiveness, assurance, empathy, and direct evidence to the community. In conclusion, there are obstacles in enhancing the organizational performance of the Puskesmas, including the lack of training and work guidance to improve competence, the lack of involvement of health workers in decision making, and the application of rewards and punishments that are still not consistently implemented. Keywords: Leadership, Performance, Quality of Service, Puskesmas